Originally Posted by

**Tygra** Hi all,

I need some help with equations such as this one:

2(4x + 3)/3 times 3(2x + 7)/4 = 72

From the above equation this is how far I have reached.

(8x + 6)/3 times (6x + 21)/4 = 72

48x^2 + 168x + 36x + 126/12 = 72

48x^2 + 204x + 126 = 72 times 12 = 864

48x^2 + 204x = 864 - 126 = 738

48x^2 + x = 738/204 = 3.617647059 **<-- please! Never do that again ...**

x^2 + x = 3.617647059/48

From here I am unsure what to do. Reverse BIDMAS says I will have to square root the square on the x last, but I still have a + x to deal with. They are not like terms so I cannot combine the x^2 + x, and I can't get rid of the square first and add the two x varables because it will mess up the eqaution and go against reverse BIDMAS.

Thanks